Fazl Ibn Ahmad: Philosophical Reflections on The Socio-Political Context of His Era - Soipova, Mavjuda (Indonesian Culture and Religion Issues, 2025)
This article provides information about the philosophical analysis of the social, economic, political, and cultural environment during the time of Fazl ibn Ahmad. The work “Iddatul Uqul” and “Umdatul Ma’qul” (The Promise of the Intellects and the Basis of What is Pleasing to the Intellect) presents thoughts on the soul, purity, spirit, and knowledge. In the process of building New Uzbekistan, the ideas of Fazl ibn Ahmad remain crucial in today’s complex era, particularly in nurturing the youth into spiritually developed individuals and raising them morally. In the current context, the effective use of Fazl ibn Ahmad’s “Iddatul Uqul” and “Umdatul Ma’qul” (The Promise of the Intellects and the Basis of What is Pleasing to the Intellect) is highlighted as a priority in social development, societal well-being, and the fulfillment of human needs.